Pemanfaatan Aplikasi Evaluasi Belajar Berbasis Web Era Covid - 19 - Arief Wisaksono; Masruchin Masruchin; Yanik Purwanti; Syarifa Ramadani Nurbaya (Universitas Muhammadiyah Yogyakarta, 2020)
Learning evaluation can provide opportunities for teachers to make plans and estimations, whether the predetermined goals will be achieved according to the planned target time. If based on the data from the evaluation results it is estimated that the goal will not be achieved as planned, the teacher would try to find the factors causing the problems found, and provide solutions to the problems. The corona pandemic period really needs an online learning and evaluation process, the use of web-based applications will be able to provide assistance to teachers who can quickly assess learning evaluations on teaching materials as well as make time efficiency. The method of making an application is by Rapid Application Development (RAD) or rapid prototype; it is a model for developing a software system with a tiered pattern. The main thing used is a tool in the form of a web-based learning evaluation application resembling an application that can carry out evaluations related to a certain exam process as a trial during entry data training of all existing subjects by the teacher concerned with the authority as a teacher, scheduling and instructor arrangement by the principal, and finally student entry by the operator. Each application a different task according to its function.